Welcome to the first issue of the College's Asia Pacific Journal of Health Management for 2024. - Neale Fong (ACHSM, 2024)
The College is going from strength to strength with membership increasing notably over the past few months and great attendance at College free webcast events as well as growing participation in other ACHSM professional development opportunities. In March a very successful one day Conference was held in Auckland, New Zealand with many from Australia and nearby countries amongst the more than 250 who attended this event. Through attending that conference, we now have 58 new College members in New Zealand who can take advantage of the benefits of College membership like this Journal, free webcasts, local networking events and access to bespoke professional development for health leaders. Our Fellowship Program for 2024 has commenced with 46 Associate Fellows applying themselves to our most prestigious capstone program. Further we have over 30 current enrolments to undertake Certification with those College members committing to maintaining their profession through the expectations of this credential. We also launched a Managing Digital Health micro credential that aligns fully with the digital health competencies in the ACHSM Master Health Service Management Competency Framework. We are in the process of distributing digital badges to all membership levels and Certified Health Managers and Executives for use on media such as LinkedIn, CVs and email signatures. These badges provide and outline of what it means to be a Fellow, Certified Health Manager or Executive of ACHSM. In this issue, as is the purpose of the Journal, there are learned articles on the importance of continuing to self-reflect on our leadership behaviours and workplace relationships. I take this opportunity of thanking Prof Mark Avery our Editor for his great work in maintaining a high quality of publication and ensuring relevancy to leaders in all sectors. I commend these to you and continue to wish you success in your ongoing leadership journey.